REINVENTING OUT-OF-HOME ADVERTISING: NAVIGATING THE 4TH INDUSTRIAL REVOLUTION - Nkosi , Thabo Mpho; van der Merwe, Sarah Jane (Ayden Journal of Management and Social Sciences, 2024)
Advertising, as a communication tool, harnesses human senses to draw attention to specific needs, products, or services, with the primary objectives of informing, persuading, and reminding. Among its various forms, outdoor advertising, also known as Out-of-Home (OOH) advertising, holds a significant historical lineage, dating back to ancient Egypt's hieroglyphics. The evolution of advertising techniques progressed significantly with Johannes Gutenberg's invention of movable type printing in the 1400s, paving the way for modern advertising mediums such as leaflets. A pivotal development occurred in 1796 with the invention of lithography, a printing process enabling the creation of posters, marking a milestone in OOH advertising history. This method utilized treated flat surfaces to selectively repel or attract ink, facilitating the mass production of visually striking advertisements. The advent of lithography heralded the rise of posters as a prominent form of OOH advertising, laying the groundwork for subsequent innovations in the field. This abstract delves into the historical evolution of outdoor advertising, tracing its origins from ancient civilizations to modern-day practices. By examining key milestones such as Gutenberg's movable type printing and the invention of lithography, the abstract elucidates the transformative impact of technological advancements on advertising mediums. Understanding the historical trajectory of outdoor advertising is crucial for contextualizing its contemporary significance and identifying emerging trends in the industry